Metals and radionuclides uptake by Ottelia alismoides collected from the ex-mining area Iin Kg. Gajah, Perak / Marlinda Musa - Musa, Marlinda (Faculty of Applied Sciences, 2008)
Heavy metals and radionuclides are naturally present in the environment. However, the anthropogenic activity may cause their content to accumulate in the environment. Due to this, the hyper-accumulation of radioactive in the environment may cause a toxic. Kg. Gajah has a lot of examining area and it has been selected as the study area. Objective of this study is to identify heavy metals and radionuclides presence in the aqua plant in the ex-tin mines in Kampung Gajah, Perak by selected Ottelia alismoides as the subject to run and also to determine the concentrations of heavy metals and radionuclides in the various part of Ottelia alismoides. The heavy metals and radionuclides selected are U, Th ,Ti, Br, La, Nd, Sm, Al, V, Mn, K, Na, Cl, and Mg. Technique use for this study is Neutron Activation Analysis (NAA). Samples were collected four times in every three months for one year duration time. The samples were dried in the oven and converts to the powder by grinder. Two irradiation procedure were used which is short radiation and long radiation before proceed to count by using gamma spectrometer. From the result, the concentration of heavy metals and radionuclides were calculation. The concentration range of U, Th ,Ti, Br, La, Nd, Sm, Al, V, Mn, K, Na, Cl, and Mg is 0.6 mg/kg to 6.2 mg/kg, 34070.6 mg/kg to 1056666 mg/kg, 621 mg/kg to 1727.7 mg/kg, 0.03 mg/kg to 0.5 mg/kg, 201.5 mg/kg to 1708 mg/kg, 10.5 mg/kg to 215 mg/kg, 5.8 mg/kg to 1157.1 mg/kg, 9017.3 mg/kg to 31182 mg/kg, 1.60 mg/kg to 12.7 mg/kg, 58.7 mg/kg to 716.6 mg/kg, 125708 mg/kg to 4305459 mg/kg, 7403 mg/kg to 10423 mg/kg, 0.0327 mg/kg to 2.24 mg/kg and 1157.5 mg/kg to 3821 mg/kg respectively. COPYRIGHT ©